An infected dentigerous cyst associated with an impacted permanent maxillary canine, inverted mesiodens and impacted supernumerary teeth - Karthik Rajaram Mohan; Balan Natarajan; Sudhaamani Mani; Yasmeen Ahmed Sahuthullah; Arivukkadal Vijaya Kannan; Haritha Doraiswamy (Wolters Kluwer Medknow Publications, 2013)
A dentigerous cyst is an odontogenic cyst associated with the crown of the impacted or unerupted teeth. Such cyst remain initially completely asymptomatic unless when infected and can be discovered only on routine radiographic examination. Here, such a case of dentigerous cyst, which was discovered on routine radiographic examination, is discussed here.